From Oversight to Governance: A Bibliometric Mapping of Internal Audit Research in Higher Education Institutions - Fury Khristianty Fitriyah (CV Putra Publisher, 2026)
This study provides a comprehensive bibliometric analysis of internal audit research within higher education institutions, mapping the intellectual structure, evolution, and emerging trends in this specialized field from 1994 to 2024. Using bibliometric analysis with the Bibliometrix R package and Biblioshiny interface, this study analyzed 162 documents from the Scopus database. The analysis employed multiple techniques including co-occurrence network analysis, thematic mapping, Bradford's Law application, and temporal evolution tracking to identify research patterns, influential works, and collaboration networks. The research reveals three distinct evolutionary phases: Foundation (1994-2010), focusing on compliance and financial controls; Growth (2011-2020), emphasizing risk management and governance frameworks; and Acceleration (2021-2024), integrating digital transformation and sustainability concerns. Analysis identified 441 contributing authors across 113 sources, with limited international collaboration (20.97%). Thematic analysis revealed four primary clusters: governance mechanisms, internal control systems, audit effectiveness, and emerging technologies. The field demonstrates a paradigm shift from traditional compliance-focused auditing to strategic governance partnership, with increasing emphasis on value creation, institutional resilience, and stakeholder accountability. Higher education institutions should reconceptualize internal audit functions as strategic governance partners rather than compliance monitors. The findings suggest the need for enhanced digital capabilities, sustainability integration, and cross-functional collaboration in audit practices. The study provides a comprehensive mapping of internal audit research specifically within higher education contexts, offering unique insights into the field's evolution and future trajectories. The multi-dimensional analysis framework contributes methodologically to bibliometric research while providing actionable intelligence for academic administrators, audit practitioners, and policy makers.